WOMEN'S LIFE IN WOMEN'S AUTOBIOGRAPHIES - Poonam Devi; Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
After studying the autobiographies of women writers of Hindi, it becomes clear that they have conveyed the experiences of reality experienced in their lives to others. Through this, women writers have done an important work of establishing their existence through writing. Autobiography has its own special place in literature. In autobiography, the qualities and defects of the writer and the life experienced by her are elaborated. The accepted story of the best autobiographies of Hindi is not just the story of one woman but the story of the whole era. In the Hindi literature, where the tradition of women's autobiography was completely lacking, now the publication of autobiographies of women writers one after the other is proof of the fact that now the bonds of social system on women have loosened somewhat.